Schistosome infection among pregnant women in the rural highlands of Madagascar: A cross-sectional study calling for public health interventions in vulnerable populations - Rakotozandrindrainy, Raphäel; Rakotoarivelo, Rivo Andry; Kislaya, Irina; Marchese, Valentina; Rasamoelina, Tahimandranto; Solonirina, Jeannine; Ratiaharison, Elveric Fesia; Razafindrakoto, Ravo; Razafindralava, Nantenaina Matthieu; Rakotozandrindrainy, Njary; Radomanana, Mickael; Andrianarivelo, Mala Rakoto; et al. (PLOS Neglected Tropical Diseases, 2024)
Author summary Schistosomiasis is a parasitic infection highly prevalent in sub-Saharan Africa and in Madagascar, where pregnant women are systematically excluded from prevention and control strategies. Our study shows the urgency for adapting public health strategies. We report a high prevalence of schistosome infection among pregnant women in Madagascar. The lack of systematic treatment for this vulnerable group can have a direct impact on the well-being of women and their offspring contributing to the vicious cycle of poverty perpetuated by schistosomiasis.